EMAIL E O ENSINO DE LÍNGUA INGLESA - Souza, Marlene de Almeida Augusto de (Intercâmbio, 2010)
In this paper I describe how I used the email to teach English in a public school in São Paulo. When I developed the activities, I intended to: make the students effectively use the language as communication means; have the teaching-learning process happening in real social context; and teach the language in a meaningful way.